Biosorption mechanism of Cr(VI) by live and heat-killed Saccharomyces cerevisiae - Xinyan Zheng; Po Hu; Ruxian Yao; Junjun Liu; Yueshuo Zhang; Hongying Mei; Qingtai Chen; Xin Du (Desalination and Water Treatment)
The biosorption mechanism of Cr(VI) by live and heat-killed Saccharomyces cerevisiae was investigated in this study. The adsorption behavior of chromium by different active cells was compared based on solution pH, biosorption time, chromium concentration, and cell concentration. The biosorption dynamic process can be categorized into three stages: rapid biosorption stage, stable precipitation stage, and further biomineralization stage. The two kinds of cells have the same ability to remove chromium ions, with the adsorption rate being above 99 % in a certain time (approximately 20 h). When the solution pH value ranged from 1.0 to 5.0, HCrO4- was identified as the main state of chromium species. Rectangular-shaped flakes with dimensions around 100 nanometers were observed on the surface of live cells, while rod precipitate appeared on the heat-killed cells’ surface. These chromium compounds may be mineralized into bentorite Ca6Cr2(SO4)3(OH)12·26 H2O (ICDD-PDF #33–0248) and chromite crystal CrO(OH) (ICDD-PDF #09–0331).